Negotiation platform for personalised advertising - Sousa, Luís Ventura de (2012)
This paper describes a multi-agent brokerage platform for near real time advertising personalisation organised in three layers: user interface, agency and marketplace. The personalisation is based on the classification of viewer profiles and advertisements (ads). The goal is to provide viewers with a personalised advertising alignment during programme intervals. The enterprise interface agents upload new ads and negotiation profiles to producer agents and new user and negotiation profiles to distributor agents. The agency layer is composed of agents that represent ad producer and media distributor enterprises as well as the market regulator. The enterprise agents offer data upload and download operations as Web Services and register the specification of these interfaces at an UDDI registry for future discovery. The market agent supports the registration and deregistration of enterprise delegate agents at the marketplace. This paper addresses the marketplace layer, an agent-based negotiation platform per se, where delegates of the relevant advertising agencies and programme distributors negotiate to create the advertising alignment that best fits a viewer profile and the advertising campaigns available. The whole brokerage platform is being developed in JADE, a multi-agent development platform. The delegate agents download the negotiation profile and upload the negotiation results from / to the corresponding enterprise agent. In the meanwhile, they negotiate using the Iterated Contract Net protocol. All tools and technologies used are open source.